The design and applications of a recursive molecular modeling framework. - Lisle, C. (IEEE Transactions on information technology in biomedicine)
In this paper, we present a recursive molecular model that is suitable for multi-resolution analysis in a variety of application areas. Our approach allows ease of use by computer scientists and biologists by proposing a software interface for molecular analysis that hides programming details. We demonstrate that our design is flexible enough for use in desktop analytical applications, in large-scale parallel simulations, and as a server for remote molecular analysis across wide-area networks.